Statistical modeling, equilibrium and kinetic studies of cadmium ions biosorption from aqueous solution using S. filipendula. Issue 3 (June 2017) - Verma, Ayushi; Kumar, Shashi; Kumar, Surendra
Highlights: Cadmium removal is studied by abundant and low cost brown alga S. filipendula . Optimization of process variables is carried out by RSM. Experimental data followed Pseudo second order kinetic and Redlich-Peterson isotherm models. Reusability of biosorbent is checked and the process is thermodynamically feasible. Abstract: In this work, S. filipendula was used as biosorbent for biosorption of Cd 2+ ions from aqueous solution in batch mode. The effect of four independent variables, initial Cd 2+ ions concentration (50–100 mg/L), pH (3–6), biosorbent dosage (0.5-1.0 g/L), and temperature (25–35 °C) on Cd 2+ ions biosorption was examined. The central composite design under response surface methodology was used to design the experimental runs and to investigate the interaction effects of variables. The biosorbent was characterized by using FESEM-EDS and FTIR techniques. Optimum values of four variables were obtained as pH (5.7), temperature (34.2 °C), initial Cd 2+ ions concentration (50.8 mg/L), and biosorbent dosage (0.99 g/L) with 99.56% removal of Cd 2+ ions. The maximum biosorption capacity was found to be 103.5 mg/g at 35 °C. The experimental data of Cd 2+ ions biosorption were fitted to six kinetic models and six isotherm models. The biosorption of Cd 2+ ions followed the pseudo second order kinetics. It confirms that chemisorption was the rate limiting step. On the basis of R 2 value close to 1.0 and very small value of Δq%, Redlich-Peterson was found as best fitted model for Cd 2+ ions biosorption. Thermodynamic study shows that Cd 2+ ions biosorption process on S. filipendula was feasible, spontaneous and endothermic in nature. Desorption study shows that after four successive biosorption-desorption cycles 81.63% and 86% of desorption and biosorption efficiency were attained, respectively. Thus, the present study proved that S. filipendula can be used as biosorbent for Cd 2+ ions biosorption from aqueous solution effectively and economically.